Determining the Dependency Structure Between Selected Macroeconomic Variables Using the Copula Method - Sozen, Mervenur; Sozen, Caglar; Seyranlioglu, Onur (Istanbul Univ, 2024)
Macroeconomic variables reflect the overall economic situation of a country over a specific period. These variables reflect a country's expectations and economic activities for the future and have great importance, particularly for a country's development, strategic planning for the future, and international competitiveness. Because macroeconomic variables are assumed to be interrelated, examining the dependency structure among these variables plays a significant role in shaping countries' economic roadmaps. The main objective of this research is to model the dependency structure between selected macroeconomic variables using the copula method. The copula method is widely used in the fields of economics and finance due to its strength in characterizing dependency among variables without requiring any assumptions. This study uses data from the Consumer Price Index (CPI), Producer Price Index (PPI), exchange rate (USD/TRY), and interest rate (real interest) between 2007-2022. The pair wise dependency structures among the CPI, PPI, exchange rate, and interest rate variables have been determined using the most appropriate copula model, and the results are then interpreted. According to the analysis results, the Joe copula model was found to best model the dependency between the paired variables of CPI and PPI, of CPI and exchange rates, of PPI and exchange rates, and of PPI and interest rates. The Gaussian copula was identified as the most suitable model for capturing the dependency between CPI and interest rates, while the Frank copula was determined to best model the dependency between exchange rates and interest rates.
Şeyranlıoğlu, Onur/0000-0002-1105-4034;
Keywords: Copula; PPI; CPI; Exchange Rate; Interest Rate